Madagascar’s agrifood system structure and drivers of transformation - Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Diao, Xinshen; Ellis, Mia (International Food Policy Research Institute, 2023)
Madagascar’s economy showed little progress during the decade from 2009 to 2019, growing at an average rate of just 2.9 percent per year, which is only marginally higher than the population growth rate of 2.7 percent (World Bank 2023). The global COVID-19 pandemic pushed the economy into negative growth in 2020, while drought, flooding, and storm damages in 2021 and 2022 had further adverse impacts on the economy. Current projections suggest the economy will achieve growth of 4.2 percent in 2023 and 4.6 percent in 2024, which are well above pre-pandemic growth rates (World Bank 2023). Agriculture is a relatively important sector in Madagascar, accounting for nearly 30 percent of GDP and more than 60 percent of employment. The poor performance of the agriculture sector in the 2009 to 2019 period—the sector grew at only 0.5 percent per year—was an important reason for weak growth overall (INSTAT 2020). In this brief, we unpack the historical and projected economic growth trajectory further to better understand the role of agriculture as well as the broader agrifood system (AFS) in the performance and transformation of the economy of Madagascar.